Correlation between Tinnitus Handicap Inventory Correlation between Tinnitus Handicap Inventory - Nyilo Purnami; Sofia Tiarini; Nico Probosutejo; Budi Utomo; Makhmudyah Indri Cahyani (PERHATI-KL, 2022)
ABSTRACTBackground: Complaints of tinnitus sufferers are generally subjective, while there is no objective examination in establishing the diagnosis of tinnitus so far, so that a questionnaire is needed to help establish it. The limitations of objectively assessing tinnitus have led to self-report questionnaires as the best option for evaluating tinnitus symptoms and measuring the extent to which quality of life is negatively impacted. Objective: to compare the scores between the Indonesian Tinnitus Handicap Inventory (THI) and the Indonesian version of the 12-item Tinnitus Primary Function Questionnaire (TPFQ). Method: A descriptive analytic study with a cross sectional design, where both variables were observed at the same time. This research was conducted at the Neurotology Outpatient Unit (URJ) RSUD Dr. Soetomo Hospital, Surabaya from September 2019 to April 2020. Result: A total of 29 tinnitus patients who met the criteria were divided by age, gender, degree of hearing loss, THI score, THI severity, and TPFQ score. Conclusion: The results of the correlation test between the degree of hearing loss with THI-Indonesia and the degree of hearing loss with the Indonesian 12-item TPFQ showed no difference in the results, namely both were not correlated, so the Indonesian 12-items TPFQ was valid and reliable, and it could be used to shorten the assessment time of tinnitus sufferers in hectic outpatient clinics. ABSTRAKLatar belakang: Keluhan penderita tinitus umumnya bersifat subyektif, sedangkan sampai saat ini belum ada sarana pemeriksaan obyektif dalam menegakkan diagnosis tinitus, maka diperlukan kuesioner untuk membantu. Keterbatasan menilai tinitus secara obyektif telah menjadikan kuesioner mandiri (self-report) sebagai pilihan terbaik untuk mengevaluasi gejala tinitus dan mengukur sejauh mana kualitas hidup terkena dampak negatif. Tujuan: membandingkan skor antara Tinnitus Handicap Inventory (THI) Indonesia dengan Tinnitus Primary Function Questionnaire (TPFQ) 12-item versi Indonesia. Metode: Penelitian ini bersifat deskriptif analitik dengan desain potong lintang, dimana kedua variabel diamati dalam waktu yang bersamaan. Penelitian ini dilakukan di Unit Rawat Jalan (URJ) Neurotologi RSUD Dr. Soetomo pada bulan September 2019 sampai dengan April 2020. Hasil: Sebanyak 29 pasien tinitus yang memenuhi kriteria dibagi berdasarkan kategori usia, jenis kelamin, derajat gangguan pendengaran, skor THI, derajat keparahan THI, dan skor TPFQ. Kesimpulan: Hasil uji korelasi antara derajat gangguan pendengaran dengan THI-Indonesia maupun derajat gangguan pendengaran dengan TPFQ 12-item Indonesia menunjukkan tidak ada perbedaan hasil, yaitu sama-sama tidak berkorelasi, sehingga TPFQ 12-item Indonesia adalah valid dan handal dapat digunakan untuk mempersingkat penilaian penderita tinitus di klinik rawat jalan yang sibuk